Florence Nightingale’s Cassandra: a transactional reading in the negotiation of meaning(s) - Araya Araya, Karla (Universidad de Costa Rica, 2011)
This article presents a literary analysis of the narrative Cassandra, by the British writer Florence Nightingale. The aim of this work is to analyze how the text structure engages the reader in a process of transactional reading to negotiate meaning(s). To do so, the theoretical framework used is the reader response criticism. This analysis includes the study of the frames developed in the text a way to confront the reader and the narrator’s worldviews, textual graphical gaps as rhetorical devise to omit information and the role of the reader as co-author of the text.